Advances in ureteral stent development. Issue 3 (May 2016) - Chew, Ben H.; Lange, Dirk
Abstract : Purpose of review: Ureteral stents are commonly used in urology, but there is no perfect ureteral stent. This review documents developing ureteral technologies and strategies over the past 2 years. This area has some progressive advances in the foreseeable future. Recent findings: Publications from 2014 and 2015 from a PubMed search with the words 'ureter' and 'stent' in the title were reviewed. Topics that affected patient symptoms from stents include selecting the proper length of stent, patient education regarding stent symptoms, and how the stent is removed. Stent extraction strings have been studied and not increased the incidence of infection or pain. There have been several publications examining antirefluxing ureteral stents that reduced vesicoureteral reflux during micturition and infection of transplanted kidneys. Other novel methods of removing a stent include new biodegradable ureteral stents and metal beads attached to the stent used in tandem with a magnetic catheter. Several new metal and mesh stents were described for use in patients with malignant ureteral obstruction. Last, new stent coatings with antimicrobial peptides have also been described. Summary: The search continues for the perfect stent and there has been promising progress over the past 2 years.